Pembunuhan Dalam Perspektif Hadis Riwayat Bukhari Muslim Dan Pasal 338 KUH Pidana - George Muhammad Maulana Helmy Gozali; Tajul Arifin (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
Murder is an act that is prohibited in Islam. One of the factors that causes someone to commit murder is low emotional control. Taking someone’s life or what is know as killing is an act that can be criminalized. The prohibition on committing murder has been regulated in Indonesian positive law and the perspective of Bukhari and Muslim Hadith. The crime of murder when viewed from the perspective of Indonesian positive law is contained in Law No. 1 of 1946 (KUHP) and in article 338. Apart from focusing from the perspective of Indonesia positive law, this research also focuses on the perspective of Islamic law and Hadith. The purpose of this article is to find out of relevance of Indonesian positive law to the Bukhari and Muslim Hadith regarding the crime of murder. In this case the author uses a descriptive qualitative research method, namely by collecting various data using literature studies. From this research, it was found that there is a connection between Bukhari and Muslim Hadith and positive Indonesian law regarding the prohibition of murder. Controlling your emotions and desires in doing everything is something you need to have as a Muslim